EFFECTIVENNES OF SKIN EXTRACT OF POMEGRANATE (PUNICA GRANATUM L) AND OLIVE OIL AS LIP MOISTURIZING (LIP BALM) - Sumitra, Jhoti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Lip balm preparatios can contain active ingredients that aim to protect the lips from extreme weather and hot sun. The active ingredient added to lip balm preparations can use natural ingredients from nature or pure chemical compounds. Natural ingredients have the advantage of having minimal side effects for long-term use. So that natural ingredients are currently the prima donna in the formulation of cosmetic preparations, including lip balm preparations. The properties of pomegranate skin protect and repair lips in lip balm preparations. pomegranate peel (Punica granatum L.) as a natural colorant and utilizes olive oil (Olive oil) as an emollient or moisturizer formulated in lip balm preparations. The results showed that all homogeneous lip balm preparations had a pH of 5.6-6.1 and were stable for 12 weeks of storage. Lip balm preparations with 10% concentration of pomegranate peel extract can provide the best lip moisturizing effect to restore lip skin once a week after application for 4 weeks. All preparations of pomegranate peel extract lip balm do not irritate the skin.